2003
DOI: 10.1074/jbc.m207926200
|View full text |Cite
|
Sign up to set email alerts
|

PepN, the Major Suc-LLVY-AMC-hydrolyzing Enzyme inEscherichia coli, Displays Functional Similarity with Downstream Processing Enzymes in Archaea and Eukarya

Abstract: Succinyl-Leu-Leu-Val-Tyr-7-amido-4-methylcoumarin (Suc-LLVY-AMC), a fluorogenic endopeptidase substrate, is used to detect 20 S proteasomal activity from Archaea to mammals. An o-phenanthroline-sensitive Suc-LLVY-AMC hydrolyzing activity was detected in Escherichia coli although it lacks 20 S proteasomes. We identified PepN, previously characterized as the sole alanine aminopeptidase in E. coli, to be responsible for the hydrolysis of Suc-LLVY-AMC. PepN is an aminoendopeptidase. First, extracts from an ethyl m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 67 publications
2
49
0
Order By: Relevance
“…This suggests that Hsp31 is a broad specificity aminopeptidase cleaving after alanine and basic amino acids. Kinetic characterization revealed that Hsp31 displays higher (24) or as the endopeptidase activity of PepN (16,17), but are much lower than the aminopeptidase activity of PepN, the major aminopeptidase of E. coli (16,17).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that Hsp31 is a broad specificity aminopeptidase cleaving after alanine and basic amino acids. Kinetic characterization revealed that Hsp31 displays higher (24) or as the endopeptidase activity of PepN (16,17), but are much lower than the aminopeptidase activity of PepN, the major aminopeptidase of E. coli (16,17).…”
Section: Resultsmentioning
confidence: 99%
“…The specific aminopeptidase activity of Hsp31 (2120 nmol/h/mg of protein), which is of the same order of magnitude as PepD (1260 nmol/h/mg of protein (24)), is considerably lower than that of PepN (2 ϫ 10 7 nmol/h/mg of protein), the major E. coli aminopeptidase (16,17). We have shown that the aminopeptidase activities assigned to Hsp31 are not contaminated by PepN by extensive purification of Hsp31 and by a different inhibitor sensitivity of Hsp31 and PepN; in contrast with Hsp31, PepN is not inhibited by EDTA or iodoacetamide but is, however, inhibited by PMSF (16 -17).…”
Section: Inhibitors Of Hsp31 Aminopeptidase Activity and Mutational Tmentioning
confidence: 99%
“…Although bacterial PepNs were initially identified as Ala aminopeptidases, subsequent studies demonstrated that Escherichia coli, Lactococcus lactis, and Streptococcus thermophilus PepNs have the highest specificities for the basic amino acids Arg and Lys, followed by hydrophobic͞uncharged residues, like Ala, Leu, Met, and Phe (4, 10). There are conflicting reports as to whether PepN has endopeptidase as well as exopeptidase activity (3,9,11). Based on biochemical studies, Chandu et al (3) have predicted two distinctive active sites, one for the well established exopeptidase activity and a second for the presumed endopeptidase activity of E. coli PepN (ePepN).…”
mentioning
confidence: 99%
“…Large complexes, such as Tricorn in archaea, further process these into peptides of 2-3 aa. Finally, various aminopeptidases and carboxypeptidases convert these into individual amino acids (3)(4)(5).…”
mentioning
confidence: 99%
See 1 more Smart Citation